The Employment of Trosborg’s Theory in Analyzing the Types and Strategies of Request Used by the Characters in Frozen II Movie Based on Their Social Contexts (A Pragmatics Approach) - Nadya Krisnanda Devi (Universitas Sebelas Maret, 2025)
This research aims to investigate and analyze the types and strategies of request used by the characters in the movie Frozen II based on their social contexts. It is aimed to find the influences of social factors (power, social distance) and movie stages (orientation, complication, evaluation, resolution) to the use of types and strategies of request by the characters of the movie using pragmatics approach based on Trosborg’s (1995) theory to reveal the types and strategies of request expressions, and the theory of social context by Brown and Levinson (1987) regarding power and social distance relationship. The results show that the use of types and strategies of request by the characters in the movie Frozen II are influenced by context of situation (power and social distance) and also the movie stages (orientation, complication, evaluation, resolution). The types and strategies of request used by the characters in each movie stage are different.